2023
DOI: 10.3390/rs15133332
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Conceptual Model for Estimating the Above-Ground Biomass of Winter Wheat Using Digital and Multispectral Unmanned Aerial Vehicle Images at Various Growth Stages

Abstract: The timely and accurate estimation of above-ground biomass (AGB) is crucial for indicating crop growth status, assisting management decisions, and predicting grain yield. Unmanned aerial vehicle (UAV) remote sensing technology is a promising approach for monitoring crop biomass. However, the determination of winter wheat AGB based on canopy reflectance is affected by spectral saturation effects. Thus, constructing a generic model for accurately estimating winter wheat AGB using UAV data is significant. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…The result showed that the different performance between SFs and TFs was stage-specific. During the early stages of crop growth, the high leaf-stem density plays a significant role in determining a substantial portion of the AGB ( Zhu et al., 2023 ). The SFs and TFs can reflect the reflectance attribute and spatial variation of rice canopy well, and the correlation between them is high ( Bai et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that the different performance between SFs and TFs was stage-specific. During the early stages of crop growth, the high leaf-stem density plays a significant role in determining a substantial portion of the AGB ( Zhu et al., 2023 ). The SFs and TFs can reflect the reflectance attribute and spatial variation of rice canopy well, and the correlation between them is high ( Bai et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…When adjusting ntree to a sufficiently large value, it primarily impacts the modeling time rather than the modeling accuracy ( Wang et al., 2016 ; Zhang et al., 2021 ). Therefore, following its application in other studies, we set ntree to 1,000 ( Li et al., 2019 ; Zhu et al., 2023 ). On the other hand, the value of mtry significantly affects the modeling accuracy of RF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, wheat cultivated within infertile acidic soil experiences a reduced protein content and growth rate and lower yields, which result in reduced profits. Soil elements such as phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), sodium (Na), nitrogen (N), and pH are vital for crop growth and often exist in low concentrations in arid and semi-arid environments [15][16][17][18]. Deficiencies of N, P, and K in soil affect wheat growth and yield drastically [19].…”
Section: Introductionmentioning
confidence: 99%
“…The common modelling approaches include parametric and non-parametric regression for crop biophysical parameter estimation. These include partial least squares regression (PLSR), random forest (RF), support vector machine (SVM), extreme gradient boosting (Xgboost), conditional inference forest (CI-forest), artificial neural network (ANN), least squares linear regression (LSLR), multiple linear regression (LR), neural network (NN), decision tree (DT), regression tree (RegT), K-nearest neighbour (KNN), boost tree (BST), and bagging tree (BagT) ensemble learning algorithms [7,18,30,[34][35][36]. PLSR provides a high level of interpretability and can overcome problems of collinearity in modelling, enhancing the accuracy of the model [9,17].…”
Section: Introductionmentioning
confidence: 99%